Desulfurization of High‐Sulfur HIsarna Hot Metal. Issue 8 (1st August 2022) - Schrama, Frank N. H.; Beunder, Elisabeth M.; Emami, Ali; Barnes, Chris M.; van Boggelen, Johan W. K.; Sietsma, Jilt; Boom, Rob; Yang, Yongxiang
Abstract : The cover shows hot metal tapped from the HIsarna Pilot Plant at Tata Steel in IJmuiden, the Netherlands. The graphs show plant data distribution for hot metal desulfurization heats with the 25 % highest and lowest specific magnesium consumption. This was part of the research to predict and control the desulfurization efficiency of high‐sulfur HIsarna hot metal. Further details can be found in article 2100398 by Schrama and co‐workers.